The Impact Of Online Commerce On Economic Growth - Endar Purnawan; Heri Triyana; Munawar Rahim (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to assess the impact of online trade through e-commerce and social commerce (s-commerce) on community empowerment and economic growth in Indonesia. This study uses a qualitative approach with a descriptive method. Primary data was obtained through in-depth interviews with small and medium enterprises (SMEs) and users of e-commerce and s-commerce platforms. Meanwhile, secondary data was collected from various relevant reports, publications and studies on the digital economy in Indonesia. Data analysis was conducted using a thematic approach to identify patterns, challenges, and opportunities in online trading activities. The results show that e-commerce and s-commerce contribute significantly to community empowerment through increased access to global markets, creation of new business opportunities, and increased income for SMEs. In addition, online commerce promotes economic inclusion by giving previously marginalized groups the opportunity to participate in the digital economy. However, challenges include limited internet access in remote areas, low digital literacy, data security risks, and digital inequality between regions. The implications of this research underscore the importance of policy interventions, such as equitable digital infrastructure development, digital skills training programs, and personal data protection, to ensure the sustainability and equitable distribution of digital economy benefits. This research contributes to understanding the dynamics of online commerce in Indonesia and offers recommendations for inclusive digital economy development.